Determination of the Critical Adiabatical Twisting Moment in the Case of Thick and Thin-Walled Metal Tubes - Śloderbach, Z.; Sawicki, T. (Engineering Transactions, 1983)
In this paper the value ot the critical adiabatical twisting moment for the case of thick- and thin-walled metal tubes is derived. The critical state means herein the maximum point of the adiabatical workhardening curve in the test of pure shearing or simple tension. The numerical results are demonstrated in a diagram form.